2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32913
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Computational Thinking in Storytelling Literacy Activities with Scratch Jr.

Abstract: Students are learning to interact with, design for, and sometimes even program computers at earlier and earlier ages. Teachers and researchers can relatively easily measure progress in learning programming tasks, but assessing conceptual understanding of computation, mainly when programming tasks are not present, is less defined or non-existent. Computational Thinking (CT) generally refers to knowledge and skills apart from, and possibly a precursor to, the ability to write computer programs, yet is commonly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Similarly, Lowe and Brophy. (2019) noted that ScratchJr is a powerful accelerator for understanding computation than abstract storytelling alone.…”
Section: Rq2: How Do Coding Apps Affect the Development Of Computational Fluency Of Young Age Students?mentioning
confidence: 83%
“…Similarly, Lowe and Brophy. (2019) noted that ScratchJr is a powerful accelerator for understanding computation than abstract storytelling alone.…”
Section: Rq2: How Do Coding Apps Affect the Development Of Computational Fluency Of Young Age Students?mentioning
confidence: 83%
“…Kazakoff also recommended ScratchJr implementation in preschool classrooms to help children acquire language and cognitive and social skills. Lowe and Brophy (2019) acknowledged the app as an accelerator for young children to understand computation in developmentally appropriate situations. They also highlighted its environment designed to inspire open-ended play.…”
Section: General Resultsmentioning
confidence: 99%
“…Lowe and Brophy (2019) acknowledged the app as an accelerator for young children to understand computation in developmentally appropriate situations. They also highlighted its environment designed to inspire open-ended play.…”
Section: General Resultsmentioning
confidence: 99%
“…Storytelling involves both reading and writing, and Scratch has been documented in literature as a novel way to promote computational thinking skills, especially with younger/early grade students (Burke, 2012;Lowe & Brophy, 2019;Smith & Burrow, 2016;Von Gillern, 2017). Smith and Burrow (2017) analyzed five and seven-year old children's use of CT skills and observed looping actions, debugging, remixing, and expression as the students generated ideas and content for their story, which are all examples of concrete CT skills.…”
Section: Storytelling With Scratchmentioning
confidence: 99%
“…Smith and Burrow (2017) analyzed five and seven-year old children's use of CT skills and observed looping actions, debugging, remixing, and expression as the students generated ideas and content for their story, which are all examples of concrete CT skills. Similarly, Lowe and Brophy (2019) concluded that computational thinking seems to be most valuable in young learners when it is grounded in concrete activities such as storytelling. They also argued that students can benefit from spending time in abstract story planning since this bears connection to decomposition and algorithm design.…”
Section: Storytelling With Scratchmentioning
confidence: 99%